The Roles of Matrilineal System Towards Integrating Religious and Cultural Values in Minangkabau Community - Handrianto, Ciptro (Jurnal Ilmiah Peuradeun, 2017)
This paper looks at one of the unique cultures of Indonesia, the Minangkabau, in West Sumatera Province. Minangkabau is known as one of the biggest cultures in the world practicing matrilineal system in its family. This system means that every child who is born follows his or her mother`s clan line. Matrilineal education integrates religious and cultural values to their children. According to this system, there are four central figures that have important roles in educating young generations of Minangkabau. They are Bundo Kanduang, Ninik Mamak, Alim Ulama, and Cadiak Pandai. The purpose of this paper is to explore the roles of these four central figures of Minangkabau in integrating religious and cultural values to the young generation. The data for this paper uses secondary data, namely the study of literature. Data analysis techniques in this study are three roots of reduction, presentation, and verification of data. Results show that each of the four central figures has different roles but they are united to integrate the education system of the Minangkabau community.